Analisis Perhitungan Margin Pembiayaan Pensiun di Bank Syariah Indonesia KCP Ambon - Ayu Sartini Kamsurya; Salma Saimima; Rosna Kurnia (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2024)
Calculation of Pension Financing Margin in the Murabahah Agreement. The type of research used is qualitative descriptive. The data collection techniques are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of the study show that the procedure/scheme for pension financing for the murabahah contract starts from an application for the purchase of goods, then the transfer of ownership directly from the supplier to the Bank. Payment is made by the Bank directly to the supplier, the customer will receive goods and documents from the supplier after entering a murabahah contract agreement with the bank, the customer pays in installments to the bank. The calculation of the margin for financing the retirement of the murabahah contract uses the flat method where from the beginning of financing to the end of financing the same installment and the margin profit is flat where it is determined at the time of the contract until the end of the installment time